Field response of wheat genotypes to spot blotch under different sowing dates at Rampur, Chitwan, Nepal - Nepal, S.; Shrestha, S. M.; Manadhar, H. K.; Yadav, R. K. (Journal of Agriculture and Forestry University, 2020)
Wheat spot blotch, caused by Bipolaris sorokiniana (Sacc.) Shoemaker has emerged as an important fungal disease for its economic losses in Nepalese wheat production system due state of poor resistance to spot blotch exacerbated by terminal heat stress in popular released wheat varieties. Thus it has engendered a dire need for identification of new robust and improved varieties with spot blotch resistance, suited to different sowing conditions. A field experiment was conducted at premises of Agriculture and Forestry University, Rampur to elucidate the field response of twenty wheat genotypes under different sowing conditions (early- 25th November, normal- 10th December, and late- 25th December) to spot blotch by using Split plot design, each treatment with three replicates, during 2017-2018. The analysis of variance revealed highly significant interaction (p<0.01) between the sowing dates and genotypes for the disease progress. A higher yield penalty due to significantly higher disease severity under late-sown wheat cropping was observed due to warmer conditions later in the season. Genotypes viz., NL 1207 (168.5 and 416.77) and BL 4341 (185.97 and 428.8) outrivaled other test genotypes with substantially lower mean area under disease progress curve (AUDPC) values based on flag leaf and penultimate leaf infection, and higher yield (3.23 and 3.02 t/ha), respectively, and thus could be effectively utilized as robust progenitor in spot blotch resistance breeding programs. Our findings revealed that the simultaneous adoption of early sowing and resistant wheat genotypes could be a promising and economic avenue to reduce the disease pressure leading reduced yield penalties.